Haiti : Sixth Review Under the Extended Credit Facility Arrangement, and Request for Extension of the Arrangement and Rephasing of Disbursements. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses Haiti's Sixth Review Under the Extended Credit Facility Arrangement, and Request for Extension of the Arrangement and Rephasing of Disbursements. Growth continued to be modest, due largely to long-standing frail capacity, weather-related shocks, and structural weaknesses. Inflation remained in the mid-single digits and international reserves at about six months of imports. Fiscal performance during the first half of the year was weaker than budgeted, mostly on account of lower revenue collection. Program implementation is broadly satisfactory. The authorities met all end-March 2013 performance criteria, but missed two indicative targets.